Greenspace planning and assessment using the normalized difference vegetation index in neighbourhoods next to Riga freeport, Latvia - Āboliņa, Kristīne; Jakovels, Dainis; Zīlāns, Andis (Landscape Architecture and Art, 2025)
In urban planning, greenspace in spatial plans is typically understood as specifically defined functional land use zones. However, in relation to the establishment of green corridors and the provision of ecosystem services as well as for the health of residents, greenery located outside of greenspace zones is equally important. In Latvia, the minimum area of greenery located on a land parcel is defined by the free area greenspace indicator. The objective of the research was to identify the changes in greenery cover on land parcels with different functional land use zoning using the normalized difference vegetation index (NDVI) method. The study was undertaken in five neighbourhoods in Riga. The results of the analyses indicate that adherence to the minimum free area greenspace indicators that are specified for different functional zones will result in a significant decrease in the amount of free area greenery in the studied neighbourhoods. The largest reduction in free area greenery is expected in non-residential functional zones. Greenspace zones, such as forest parks and parks, which are to undergo major upgrades in recreational ammenities, will experience a reduction the size of the natural areas by as much as one third. The application of the NDVI method is well-suited for monitoring the amount and distribution of urban vegetation cover and for assessing spatial development at the neighbourhood level. However, due to the structure of existing zoning regulations in Riga, which can differ at the level of individual land parcels, the systematic application of the NDVI method in Riga is not presently possible.